Spherulite Growth Rate in Polypropylene/Silica Nanoparticle Composites: Effect of Particle Morphology and Compatibilizer - Zapata-Ramirez, P (2011)
Spherical and tube-like (TL) silica nanoparticles were melt blended with an isotactic polypropylene (PP) matrix and its effect on the isothermal spherulite growth rate was analyzed by polarized optical microscope. The addition of low amount (?1 wt.-%) of either 15 nm spherical or TL particles raises the spherulite growth rate and the nucleation density of spherulites. Samples prepared with silica spheres of 80 nm otherwise do not show any change in the crystallization behavior. By adding a compatibilizer, both the nucleation density and the spherulite growth rate of the pure polymer are increased. Noteworthy, although the nanoparticles do not further increase the nucleation density of the PP/compatibilizer blend, independent of its form and size, they cause a decrease in its spherulite growth rate.(Figure Presented) Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: crystallization; nanocomposites; poly(propylene); spherulites